Divergent oral cavity motor strategies between healthy elite and dystonic horn players. Issue 1 (December 2015) - Iltis, Peter; Frahm, Jens; Voit, Dirk; Joseph, Arun; Schoonderwaldt, Erwin; Altenmüller, Eckart
Abstract Background This paper describes the use of real-time magnetic resonance imaging in visualizing and quantifying oral cavity motor strategies employed by 6 healthy, elite horn players and 5 horn players with embouchure dystonia. Methods Serial images with an acquisition time of 33.3 ms were obtained from each performer during execution of an 11-note harmonic series encompassing 2.5 octaves on a magnetic resonance imaging-compatible horn. A customized MATLAB toolkit was employed for the extraction of line profiles from magnetic resonance imaging films allowing comparative analyses between elite and dystonic horn players. Results The data demonstrate differing motor strategies, particularly in moving from the 6th through 9th harmonics. The elite horn player strategy features elevation and anterior displacement of the tongue during ascending sequences, whereas dystonic players showed significantly less movement. The elite horn players thus narrowed the air channel on higher notes, presumably affording faster airflow for vibration of the lips at higher frequencies. Conclusions We postulate that failure to employ this strategy by dystonic horn players may require greater tension in the embouchure muscles to compensate for slower air speed. Though this may simply be an expression of or adaptation for dystonia, the possibility that it may be a contributing factor in the development of embouchure dystonia is suggested.